ANALYSIS OF COST AND TIME TRAVEL SATISFACTION LEVEL OF PASSENGER TRANSPORT IN THE RIVER KATINGAN OF CENTRAL KALIMANTAN - Whendy Trissan (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
This study aims to make an analysis of passenger satisfaction river transport modes by using stated preference techniques, where repsonden declare his choice based on current conditions and expected conditions (imaginary). The study was conducted in order to know how much influence the level of willingness of passengers to services in the transport stream as well as modeling the utility rate of passenger transport modal choice Klotok rivers and speed boats. In the analysis of passenger satisfaction river transport modes is based on the theory of the selection of discrete (discrete choice) using a binomial logit models and data analysis using statistical software version 7.0 . Statistical analysis of the results states that Chi-Squared (X2 ) of = 171.9939. The overall success index (Ti) = 0.216. From the analysis of data obtained probability value for modes Speedboat by 0.72 and Klotok by 0.28. The results of the model application with a few scenarios of changes in costs and travel time cost attribute indicate that the change is more sensitive to changes in probability.